(untitled) - Siciliano, Tom (San Francisco, 2005)
Discover this step-by-step plan to match your strengths and interests with a career that will fulfill you for a lifetime. Shifting into Higher Gear creates a pathway to minimize the stress and confusion of seeking the right job. The book presents a comprehensive three-stage program for discovering your calling, turning that calling into a career, and sustaining your passion once youre in the job of your dreams. Grounded in Biblical wisdom, yet highly practical, the book is packed with field-tested advice, worksheets, self-assessments, and creative questions for action and reflection. This is must-read will become a trusted "owners manual" for a lifetime of meaningful work.
Keywords: Vocational guidance,Career development,Job hunting